'Thou Hast Forsaken Thy First Love': Soteriological Contingency in the Book of Revelation - Quient, Nicholas Rudolph (Evangelical review of theology, 2019)
The article focuses on the exegesis of the passages found in the book of Revelation noting salvation as a contingent. Topics discussed include an overview of the soteriological contingency, its predetermination, the totality of the New Testament, its dynamics, and its determinism involving the deterministic models within the theological systems.